Colorectal cancer surgery in Serbia 2010–2014: An evaluation of a multicenter registry - Nikolić, Aleksandra; Krnjajić, Mina; Marković, Velimir; Barišić, Goran; Dimitrijević, Ivan; Krivokapić, Zoran (Vojnosanitetski pregled, 2021)
Background/Aim. Surgical registries and databases are especially valuable in monitoring the performances in cancer treatment and detecting potential problems. For Serbian patients with colorectal cancer (CRC), data regarding the treatment received, the factors that may impact the outcome, and whether or not treatment is successful and appropriate are not currently captured. The aim of this study was to establish a collection of a consensus dataset capturing surgical treatment of CRC at multiple public hospitals across Serbia and estimate outcome in CRC patients subjected to surgical treatment in the period 2010–2014. Methods. The study encompassed all 52 public CRC surgical units in Serbia. Numerical data on all patients who underwent operative CRC resection were included. An electronic database was created and overseen by the First Surgical Clinic of the Clinical Center of Serbia, Belgrade. Data were collected independently using a specifically designed standardized questionnaire, including the number of operated patients, localization of the primary tumor, type of surgical intervention, type and urgency of surgical intervention, and postoperative mortality. Results. A total number of 22,037 colorectal surgical procedures was performed in Serbia in the period 2010–2014 (approximately 4,400 per year). It was shown that 78.5% of the total number of procedures were elective and 21.5% were emergency. The most common cause of emergency surgeries was ileus (3,618 cases, 76.4%), while the less common causes were perforation (899 cases, 18.9%) and bleeding (216 cases, 4.5%). Postoperative mortality during the study period expressed as a percentage of all interventions for CRC was 2.8% on average with a slight increasing tendency. At the end of the study period, 127 doctors were educated for performing colonoscopy. Conclusion. The main outcome of this study was the establishment of the necessary preconditions for the multicenter data collection involving large numbers of CRC patients. The study supported the premise that the development of the national database for surgical treatment of CRC is achievable and could provide valuable insight into the routine surgical management of CRC in Serbia, creating a significant resource for further research.
Keywords: colorectal neoplasms; database as topic; general surgery; mortality; serbia; surgical procedures, operative; surveys and questionnaires